Collaborative Governance in Nagari Development in Nagari Tigo Balai, Matur District - Arfita, Sintari; Valentina, Tengku Rika; Putera, Roni Ekha (JAKPP (Jurnal Analisis Kebijakan & Pelayanan Publik), 2023)
This study explores the implementation of collaborative governance in village development in Nagari Tigo Balai, Matur District, a locality recognized for its excellence in village financial management and fiscal transparency. Using a qualitative case study approach, the research analyzes how key collaborative governance principles are applied across the planning, implementation, and monitoring stages of local development. The findings reveal that five critical factors—willingness to compromise, effective communication, mutual commitment, trust, and information sharing—consistently shape stakeholder collaboration during all phases of the development process. These elements foster inclusive participation and strengthen transparency in local governance practices. However, the study also identifies inhibiting factors, including limited innovation in village development strategies and insufficient openness in financial disclosures by the nagari government. This research contributes to broader discussions on participatory governance and decentralized development in emerging economies. It provides practical insights into how collaborative governance can enhance administrative accountability and community engagement, particularly in culturally rooted governance systems beyond the Western context.